The cost of conditional cash transfers - Caldés, Natàlia; Maluccio, John (Wiley, 2005)
A common criticism of antipoverty programs is that a large proportion of their budgets never reaches the intended beneficiaries but is absorbed by administration costs. Yet, there is little empirical evidence on the costs, and even less on the cost structures, of such programs. This paper outlines and implements a replicable methodology for a disaggregated cost analysis of a pilot conditional cash transfer program in Nicaragua, examining the administration and private costs associated with a one-unit transfer to a beneficiary—referred to as the cost-transfer ratio. We find that for a meaningful assessment of cost-efficiency, it is misleading to make calculations using only the typically available raw accounting data. Rather, one must delve into the details and specific activities of the program. This is particularly important for pilot programs, which typically have many up-front fixed costs associated with design and setting up operations. It is also important for conditional cash transfer programs, which have additional costs associated with their specific design features and require changes in beneficiary behavior that may engender substantial private costs.